2014
DOI: 10.1002/anie.201404094
|View full text |Cite
|
Sign up to set email alerts
|

The Asymmetric Hetero‐Diels–Alder Reaction in the Syntheses of Biologically Relevant Compounds

Abstract: The hetero-Diels-Alder reaction is one of the most powerful transformations in the chemistry toolbox for the synthesis of aza- and oxa-heterocycles embodying multiple stereogenic centers. However, as compared to other cycloadditions, in particular the dipolar cycloadditions and the Diels-Alder reaction, the hetero-Diels-Alder reaction has been much less explored and exploited in organic synthesis. Nevertheless, this powerful transformation has opened up efficient and creative routes to biologically relevant sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(61 citation statements)
references
References 89 publications
0
60
0
1
Order By: Relevance
“…Forpractical reasons,itisworth noting that this new asymmetric photoreaction can be scaled up.On ascale of 4.5 mmol (1.08 g), the reaction 1d!2d afforded an improved yield of 90 %with aslightly increased enantiomeric excess of 99 %a nd the rhodium catalyst was reisolated in 86 %yield by capture with an auxiliary ligand in aprocedure reported recently. [9,10] An intersystem crossing to the singlet-state ketene IV sets the stage for an intramolecular asymmetric hetero-Diels-Alder reaction [11] to form the rhodium bound cyclopropane product VI.P roduct release and recoordination of new substrate then initiates anew catalytic cycle. The catalytic cycle starts with the rhodium catalyst binding to the N-acyl pyrazole substrate in ab identate fashion (int.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Forpractical reasons,itisworth noting that this new asymmetric photoreaction can be scaled up.On ascale of 4.5 mmol (1.08 g), the reaction 1d!2d afforded an improved yield of 90 %with aslightly increased enantiomeric excess of 99 %a nd the rhodium catalyst was reisolated in 86 %yield by capture with an auxiliary ligand in aprocedure reported recently. [9,10] An intersystem crossing to the singlet-state ketene IV sets the stage for an intramolecular asymmetric hetero-Diels-Alder reaction [11] to form the rhodium bound cyclopropane product VI.P roduct release and recoordination of new substrate then initiates anew catalytic cycle. The catalytic cycle starts with the rhodium catalyst binding to the N-acyl pyrazole substrate in ab identate fashion (int.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Notably,t he successful multicomponent reaction of unsaturated aldehydes proceeded with excellent results (entries 5a nd 6). More significantly,a liphatic aldehydes performed well in the reaction (entries [7][8][9][10][11][12]. In particular, the introduction of different functionalities to the aliphatic aldehydes was nicely accommodated and yielded multiply functionalized chiral homoallylic alcohols with excellent selectivities (entries 9-12).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[12] Very recently,T oste and co-workers showed that the chiral ion pair 2' ' (Scheme 2), generated from am etathesis reaction of the insoluble aryldiazonium salt 2 and chiral phosphate salt by phase transfer (CAPT), [11] was able to undergo oxidative addition with the palladium(0) A species to give the chiral aryl palladium(II) phosphate B. [13] We and others previously found that the aryl palladium(II) species could undergo migratory insertion of a1 ,3-diene to generate a p-allyl palladium intermediate.…”
mentioning
confidence: 99%
“…In that case, the asymmetric version is of special importance [3]. The most frequently reported hetero-Diels-Alder reactions belong to the so-called aza-or oxa-types with the C=N or C=O units in the diene or dienophile.…”
Section: Introductionmentioning
confidence: 99%